2022
DOI: 10.1002/fsn3.2733
|View full text |Cite
|
Sign up to set email alerts
|

8‐Prenylnaringenin tissue distribution and pharmacokinetics in mice and its binding to human serum albumin and cellular uptake in human embryonic kidney cells

Abstract: 8‐Prenylnaringenin (8‐PN), a hop flavonoid, is a promising food substance with health benefits. Compared with nonprenylated naringenin, 8‐PN exhibits stronger estrogenic activity and prevents muscle atrophy. Moreover, 8‐PN prevents hot flushes and bone loss. Considering that prenylation reportedly improves the bioavailability of flavonoids, we compared the parameters related to the bioavailability [pharmacokinetics and tissue distribution in C57/BL6 mice, binding affinity to human serum albumin (HSA), and cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 72 publications
1
8
0
Order By: Relevance
“…When further cellular distribution was examined by fluorescence microscopy and compared to naringenin, the distribution of fluorescence was clearly confirmed (Figure 4). Tanaka et al reported that the cellular uptake of 8-PN in HEK293 cells was higher than that of naringenin [39], and similar results were obtained in MDCK cells. While 8-PN was localized throughout the nucleus and cytoplasm, 6-PN was localized in the periphery of the cytoplasm.…”
Section: Discussionmentioning
confidence: 55%
“…When further cellular distribution was examined by fluorescence microscopy and compared to naringenin, the distribution of fluorescence was clearly confirmed (Figure 4). Tanaka et al reported that the cellular uptake of 8-PN in HEK293 cells was higher than that of naringenin [39], and similar results were obtained in MDCK cells. While 8-PN was localized throughout the nucleus and cytoplasm, 6-PN was localized in the periphery of the cytoplasm.…”
Section: Discussionmentioning
confidence: 55%
“…Quercetin has been reported to improve muscle mass and mitochondrial content, particularly in conditions like cancer and chemotherapy-induced cachexia (VanderVeen et al, 2022). On the other hand, 8-Prenylnaringenin, a hop flavonoid, has been identified as a food substance with health benefits (Tanaka et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…In their study on the tissue distribution and pharmacokinetics of 8-PN versus naringenin in mouse models, Tanaka et al (2021) found the highest accumulation of 8-PN in the kidney and a significant accumulation in skeletal muscle. The authors also observed that 4 h after the ingestion of an average daily dose of 4.4 g/day/mouse of 8-PN, its plasma concentration increased and remained high up to 8 h after ingestion, being detectable even 24 h after and undetectable only after 48 h [158].…”
Section: Pharmacokinetics Of Bioactive Hop Compoundsmentioning
confidence: 86%